Theorizing Moral Cognition: Culture in Action, Situations, and Relationships - Aliza Luft (Socius, 2020)
Dual-process theories of morality are approaches to moral cognition that stress the varying significance of emotion and deliberation in shaping judgments of action. Sociological research that builds on these ideas considers how cross-cultural variation alters judgments, with important consequences for what is and is not considered moral behavior. Yet lacking from these approaches is the notion that, depending on the situation and relationship, the same behavior by the same person can be considered more or less moral. The author reviews recent trends in sociological theorizing about morality and calls attention to the neglect of situational variations and social perceptions as mediating influences on judgment. She then analyzes the moral machine experiment to demonstrate how situations and relationships inform moral cognition. Finally, the author suggests that we can extend contemporary trends in the sociology of morality by connecting culture in thinking about action to culture in thinking about people.